Contribution of indigenous banks to economic development in the Caribbean : the case of Guyana - Russell, Patsy ([CCMS] [St. Augustine]TT, 2001)
Examines the contribution of one of the indigenous banks in Guyana, the Guyana National Cooperative Bank, towards the economic growth and development of that country.